The Brazilian Landless Movement (MST): critical times - Navarro, Zander (Redes, 2010)
This paper summarizes core aspects that marked the history of the Brazilian Landless Movement (MST), in recent years. It tries to demonstrate that nowadays the organization is experiencing mounting impasses, in part because of urbanization and its impacts on social perceptions about the trajectory of land reform in Brazil. Typical problematic aspects of the Movement are checklisted and briefly discussed, from organizational choices to the MST’s controversial repertoire of struggles implemented to enhance its political clout. The text also refers to challenges recently observed, which threatens the very existence of the organization in the near future.